Das 6. Batallion . The 6th Battalion - Šimko, Dušan (Switzerland, 1997)
Soros Documentary Fund The film documents the fate of 1200 Jewish men in Slovakia, during WWII, who were forced to join the 6th army Brigade of the fascist Slovak state between 1939-1945. Rich in archival footage, the film recounts their stories via interviews.